Perception of Intelligent Packaging in the Context of Bioeconomy - Loučanová , Erika; Parobek , Ján; Nosáľová , Martina; Dopico, Ana; Hupková , Daniela (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2020)
The research of new intelligent features has shown huge potential to optimize the supply chain and enhance consumer consciousness of product utilization. The implementation of bioeconomy principles in all sectors is essential in seeking to achieve Sustainable Development Goals. Innovation in the packaging industry can be considered as one of the key sectors in this approach. The study deals with the evaluation of the perception of intelligent packaging in Slovakia as ecological innovations through the Kano model. The results indicate that customer awareness of intelligent packaging as ecological innovation in the context bioeconomy is still at a low level in Slovakia. Hdgdgdsgowever, from the point of view of intelligent packaging, Slovak customers represent a key element of stakeholders for the management of innovation processes towards bioeconomy criteria.